Dampak Kompensasi, Lingkungan Kerja Non Fisik dan Kepuasan Kerja terhadap Retensi Karyawan di PT. Riau Food Lastari - Adinda, Aisyah Tri; Emilda, Emilda; Darmaputera, Mohammad Kurniawan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2025)
Employee retention will increase when employees feel satisfied with their jo. To encourage employee retentuin, companies must be able to respond to employees needs,inculding compensastion, the physical work environment and job satusfaction. This study aims to examine the impact of compensation, non-physical work environment, and job satisfaction on employee retention at PT. Riau Food Lastari Palembang. This research employs a quantitative method with a total 65 population and sample of 65 employees, selected using purposive sampling. The results indicate that compensation, non-physical work environment, and job satisfaction simultaneously have a significant effect on employee retention. Partially, the non-physical work environment has the most substantial impact compared to other variables.